Factors affecting the relationship of bond work grindability and abrasion indices of calcite, silica, and chromite - Buenaventura, Brian Milo H. (2011.)
The study aims to investigate factors affecting the relationship between two (2) comminution Bond indices in mineral processing, namely, work grindability index and abrasion index. These factors include mineral hardness (Mohs, H), competency and rate of breakage, specific gravity, and shape factor. Three (3) minerals are investigated, namely: Calcite (H = 3), Chromite (H = 5.5), and Silica (H = 6). A Bond Abrasion Tester is fabricated und calibrated for the study. The standard Bond Grindability Index Ball Mill is used to determine the work indices of each of the minerals. SEM-EDX analysis is performed on the minerals to determine their chemical composition and surface microstructure. The Bond work indices of calcite, silica, and chromite ure delermined to be 7.86 kWhr/Mt, 9.17 kWh/Mt, and 9.94 kWh/Mt, respectively, while the abrasion indices are likewise determined to be 0.0097 g, 0.2030 g, and 0.2 772 g, respectively. A modified method in abrasion testing, where the time of comminution is varied for 15, 45, 90, and 150 minutes, was used to monitor changes in the behavior on the minerals in terms of particle size distribution and particle shape per size fraction. The shape factor, which includes properties such as circularity, roundness, and waviness, is analyzed using image analysis software (ImageJ). Mineralogical analyses showed that calcite having a distinct crystallinity exhibited a different breakage mechanism compared to chromite and silica. Shape analysis showed that circularity did not exhibit a clear trend in the abrasion responses of the three (3) minerals, buti it confirmed with the breakage mechanism of calcite due to its mineralogical structure. Both roundness and waviness showed decreasing trends wilh a corresponding decrease in the abrasiveness of the minerals. Increased angularity and roughness of Ihe minerals resulted in greater metal wear due to the presence of more stress-concentration points thus higher abrasion readings. Shape factor, combined with the work index factors such as the rate of reduction, hardness, and specific gravity, is explained by the impulse-momentum principle to show the mechanics of metal wear (abrasion) as caused by impact (work grindability).
Thesis (M.S. Metallurgical Engineering)--University of the Philippines, Diliman.
Keywords: Ore-dressing.; Silica; Chromite; Calcite